Theorising participation as communicative action for development and social change - Hannelie Otto; Lynette Fourie (Communicare)
This article explores, through a basic conceptual-theoretical analysis and a review of relevant literature, the usefulness of employing the communicative action theory of Jürgen Habermas in theorising the elusive notions of participation and participatory communication theory as applicable to project based development (Burnside-Lawry, 2012; Chang & Jacobson, 2010; Jacobson, 2003; Jacobson & Storey, 2004; Ramella & De La Cruz, 2000; Servaes, 1999). The problem with defining participation is that it is ambiguous – both notionally and in actual contexts – as the concept comprises a myriad of dissimilar epistemologies, methodologies and imagined goals, while also representing disparate evaluative measures in thinking about and determining whether or not participation has actually occurred in its various applied settings (Chitnis, 2005; Huesca, 2008; Jacobson & Storey, 2004; McAnany, 2012; Melkote & Steeves, 2001; Morris, 2003; Wilkins, 2000).